Implementation of Orderly Policy for Public Facilities in Tomohon City - Mandagi, Octavianus D.S.; Bogar, Wilson; Pangkey, Itje (Technium Social Sciences Journal, 2021)
The development of Tomohon City will be able to take place sustainably and increase if it is supported by the existence of conducive public order and community peace. For this reason, the Tomohon City government establishes an orderly policy for public facilities in the form of regional regulations to regulate them. This study aims to describe, analyze and explain policy implementation orderly public facilities in accordance Regulation of Regional No. 7 of 2017 on article 3 in Tomohon. The research method uses a qualitative approach, and informants as data sources are determined by purposive (purposive sampling) and snowball sampling—data collection techniques with interviews, observations, and documents. Data analysis is an interactive qualitative analysis with data analysis activities, namely data reduction, data presentation, and concluding/verification. The results showed that (1) the size and purpose of the orderly policy of public facilities had been known and understood by members of the civil service police unit (implementor) and the community (users), (2) Resources, both human resources (police unit members/ civil service), sources of funds and equipment/equipment needed by the civil service police unit are still inadequate, (3) the characteristics of the implementing agent, in this case, the civil service police unit institution are still receiving a preliminary assessment from the public, (4) the tendency (Disposition) the implementers, in this case, members of the civil service police unit, are still not firm and consistent in controlling violations of the order of public facilities, (5) communication between related organizations, such as the police, sub-district government and social organizations in the village well-established, (6) Economic, Social and Political Environment is a crucial factor his contribution to the community violates the order of public facilities.